109 Neonatal Cerebral Oxygenation is Associated with Neurodevelopmental Outcome of Preterm Infants at 2 to 3 Years of Age. (October 2012) - Verhagen, EA; Braeckel, KNJA Van; Veere, CN van der; Groen, H; Dijk, PH; Hulzebos, CV; Bos, AF
Abstract : Background and aims: Disturbed cerebral oxygenation during the neonatal period might pose preterm infants at risk for neurological deficits. Our aim was to determine whether regional cerebral tissue oxygen saturation (rc SO2 ) and fractional tissue oxygen extraction (FTOE), measured by near-infrared spectroscopy, were associated with neurodevelopmental outcome of preterm infants at 2–3 years of age. Methods: We included 83 preterm infants (gestational age< 32 weeks) and measured rc SO2, and calculated FTOE on days 1, 2, 3, 4, 5, 8, and 15 after birth: (tcSaO2 -rc SO2 )/tcSaO2 . Additionally, we determined the area under the curve (AUC) of rc SO2 and FTOE during the first 2 weeks. Cognitive, motor, neurological and behavioural outcome was determined at 2–3 years of age. Multiple linear regression analyses were used to determine whether rc SO2 and FTOE contributed to outcome. Results: We included 67 infants for follow-up. Lower quartile (P25–50 ) and highest quartile (P75–100 ) of rc SO2 values on day 1 were associated with poorer cognitive outcome (p=0.044 and p=0.008, respectively). Lower AUC of rc SO2 was associated with poorer cognitive outcome (p=0.014). Lower quartile (P25–50 ) AUC of rc SO2 was associated with poorer fine motor outcome (p=0.004). The amount of time rc SO2 < 50% on day 1 was negatively associated with gross motor outcome (p=0.002). The highest quartile of FTOE values on day 1 was associated with poorer total motor outcome (p=0.041). Conclusions: Neurodevelopmental outcome at 2–3 years of age was associated with cerebral oxygen saturation during the first 2 weeks after birth in preterm infants. Both high and low rc SO2 values had a negative influence on neurodevelopmental outcome.